Population dynamics of Brachiaria plantaginea (Link) Hitch. by soil and herbicide managements. I. Survival - Voll, Elemar; Gazziero, Dionísio L. P.; Karam, Décio (Pesquisa Agropecuaria Brasileira, 1995)
A field experiment was carried out in Londrina, Paraná State, Brazil, on a "Latossolo Roxo distrófico". The objective was to determine the survival period of Brachiaria plantaginea (Link) Hitch. for predictive management uses in weed control. Soil and herbicide managements in soybeans, followed by wheat, were established during five years. Survival periods were higher in disc plowing, or conventional tillage (CT), and in moldboard (MT), of 12.2 and 11.5 years, respectively; intermediary, of 7.5 years, by scarification and heavy discs (SHD) and lower, of 5.2 years, in no-till (NT). Annually decreasing and increasing rates of seeds in soil were exponential and, respectively, of 31.7% and 32.6% in CT; 33.2% and 25.0% in MT; 45.8% and 45.5% in SHD, and 58.9% and 46.0% in NT. Seed concentration at 0- 10 cm layer was over 90%. Liming operations done before wheat sowing reduced seedbank in soil. Physiologic evaluations of soil seeds through germination rate, germination velocity and electric conductivity showed trends to variation with managements. Laboratory germination rate was averaged in 83.8%.